Corrosion morphology of aluminium sacrificial anodes. Issue 12 (17th July 2013) - Pourgharibshahi, M.; Meratian, M.
<x xml:space="preserve">Abstract</x> Corrosion morphology and electrochemical performance of five different cast Al alloys were investigated. A short‐term electrochemical test according to the DNV‐RP‐B401 standard was used to investigate electrochemical performance of these alloys. Scanning electron microscopy and inductively coupled plasma mass spectrometry were employed to gain knowledge of the morphology and corrosion process of the Al alloys. Producing high performance aluminium anodes by metal mould casting technique needs several alloying elements (like silicon, magnesium and calcium) other than just zinc and indium. A cast aluminium sacrificial anode with appropriate electrochemical properties and composition of Al–5.5%Zn–0.35%Si–0.1%Mg–0.1%Ca–0.02%In was introduced.